The Relationship Between Learning Motivation and Sources of Information About Reproductive Health with Adolescent Sexual Behavior - Nurianti, Irma; Saputri, Ika Nur; Telova, Yurizki; Simargolang, Inda Andini (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2024)
The increase in adolescent reproduction-related cases is currently a serious concern, and one contributing factor is adolescents' lack of understanding of various aspects of reproduction related to themselves. This phenomenon has resulted in an increase in adolescent problems, such as pregnancies out of wedlock, incidents of rape during dating, and an increase in sexually transmitted diseases. This can be attributed to a lack of awareness and understanding of proper sexual behavior among adolescents. This study aims to identify the relationship between learning motivation and sources of information about reproductive health with adolescent sexual behavior at Smk Al-Washliyah 9 Perbaungan This type of research uses quantitative methods with a cross sectional approach. A sample of 36 respondents was taken using purposive sampling techniques. Based on the results of the data obtained, it was concluded that learning motivation and sources of information about reproductive health are related to adolescent sexual behavior. This can be seen from the P-value of 0.033 which means smaller than ? (0.05). So it was concluded that there is a relationship between learning motivation and Chi-Square test results show a P-value of 0.018, which is smaller than the significance level of ? (0.05). Therefore, it can be concluded that there is a significant relationship between sources of information about reproductive health and adolescent sexual behavior at SMK Al-Washliyah 9 Perbaungan.